2019
DOI: 10.1002/jcp.28973
|View full text |Cite
|
Sign up to set email alerts
|

LINC00324 accelerates the proliferation and migration of osteosarcoma through regulating WDR66

Abstract: Osteosarcoma (OS) is a type of malignancy featured with high morbidity and easy metastasis. Although past years have witnessed the great improvement in the treatments of OS, there remains a long way to go. Therefore, further research on the underlying molecular mechanism of OS progression is in imminent need. Long noncoding RNAs (lncRNA) are recognized as a cluster of transcripts over 200 bases.Increasing studies have unveiled their significant regulatory roles in cancers, including in osteosarcoma. Long inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 31 publications
(72 reference statements)
1
32
2
Order By: Relevance
“…Previous researches have confirmed that LINC00324 takes part in cell proliferation, invasion, and migration in cancer. Wu et al have proven that LINC00324 increases the proliferation and migration of osteosarcoma cells via targeting WDR66 [9]. Pan et al have shown that LINC00324 has the ability to promote the growth of lung adenocarcinoma through regulating the miR-615-5p/AKT1 axis [8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous researches have confirmed that LINC00324 takes part in cell proliferation, invasion, and migration in cancer. Wu et al have proven that LINC00324 increases the proliferation and migration of osteosarcoma cells via targeting WDR66 [9]. Pan et al have shown that LINC00324 has the ability to promote the growth of lung adenocarcinoma through regulating the miR-615-5p/AKT1 axis [8].…”
Section: Discussionmentioning
confidence: 99%
“…Recently, some studies have indicated that LINC00324 is involved in cancer progression. For example, LINC00324 increases the proliferation and migration of osteosarcoma cells [9]. LINC00324 promotes the tumorigenesis of lung adenocarcinoma [8].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies indicate that aberrant expression of lncRNAs facilitates OS development (Ren et al, 2019;Wu et al, 2020;Yang et al, 2019;Zhang et al, 2019). These lncRNAs exert their functions by several mechanisms, including targeting some host genes, involvement with signaling pathways and competing with endogenous miRNA.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, expression of LINC00324 has been validated as an independent predictive factor of overall survival and disease-free survival among patients with gastric cancer [26]. LINC00324 is also overexpressed in lung adenocarcinoma [27] and osteosarcoma [28]. Overexpression of LINC00324 is closely associated with tumor size, distant metastasis, TNM stage, differentiation degree, and poor prognosis among patients with osteosarcoma [28].…”
Section: Agingmentioning
confidence: 99%
“…Long intergenic non-protein-coding RNA 324 (LINC00324) is abnormally expressed in multiple human cancer types [26][27][28] and performs important functions in cancer initiation and progression. Nevertheless, the expression profile, clinical relevance, specific effects, and regulatory mechanisms underlying the action of LINC00324 in RB have not been fully elucidated.…”
Section: Introductionmentioning
confidence: 99%